ZEB2 in T-cells and T-ALL. (December 2019) - De Coninck, Stien; Berx, Geert; Taghon, Tom; Van Vlierberghe, Pieter; Goossens, Steven
Abstract: The identification of the rare but recurrent t(2; 14)(q22; q32) translocation involving the ZEB2 locus in T-cell acute lymphoblastic leukemia, suggested that ZEB2 is an oncogenic driver of this high-risk subtype of leukemia. ZEB2, a zinc finger E-box homeobox binding transcription factor, is a master regulator of cellular plasticity and its expression is correlated with poor overall survival of cancer patients. Recent loss- and gain-of-function in the mouse revealed important roles of ZEB2 during different stages of hematopoiesis, including the T-cell lineage. Here, we summarize the roles of ZEB2 in T-cells, their development, and malignant transformation to T-ALL.